Does test-based teacher recruitment work in the developing world? Experimental evidence from Ecuador - Maria Daniela Araujo P.; Guido Heineck; Yyannú Cruz Aguayo (Bamberg University, Bamberg Economic Research Group (BERG), 2020)
Since 2007, the Ecuadorian government has required teacher candidates to pass national skill and content knowledge tests before they are allowed to participate in merit-based selection competitions for tenured positions at public schools in an attempt to raise teacher quality. We evaluate the impact of this policy using linked administrative teacher information to data from a unique experimental study where almost 15,000 kindergarten children were randomly assigned to their teachers in the 2012-2013 school year in Ecuador. We find positive and significant effects of testscreened tenured teachers of at least a 0.105 standard deviation for language and a 0.085 standard deviation for math, which persist even after controlling for teacher education, experience, cognitive ability, personality traits and classroom practices.
Keywords: I20; I21; I25; I28; J45; 330; teacher quality; education policy evaluation; Latin America